PRECEPTS, POLICY AND PROCESS: PERSPECTIVES ON CONTEMPORARY CANADIAN EDUCATION (Authors: Hugh A. Stevenson and J. Donald Wilson) - Gillett, Margaret (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1978)
Hugh A. Stevenson and J. Donald Wilson. PRECEPTS, POLICY AND PROCESS: PERSPECTIVES ON CONTEMPORARY CANADIAN EDUCATION. London, Ontario: Alexander, Blake, 1977. 354 pp. $8.95 paper.